Holography Different Fields of Application - Alberto Monroy Ramirez, Freddy (IntechOpen, 2011)
This book depicts some differences from the typical scientific and technological literature on the theoretical study of holography and its applications. It offers topics that are not very commercial nor known, which will allow a different view of the field of optics. This is evident in chapters such as "Electron Holography of Magnetic Materials", "Polarization Holographic Gratings in Polymer Dispersed Formed Liquid Crystals", and "Digital Holography: Computer-generated Holograms and Diffractive Optics in Scalar Diffraction Domain". The readers will gain a different view of the application areas of holography and the wide range of possible directions that can guide research in the fields of optics.